FAKTOR-FAKTOR YANG MEMPENGARUHI RETURN AWAL PADA PERUSAHAAN YANG MELAKUKAN PENAWARAN UMUM PERDANA DI BURSA EFEK INDONESIA PERIODE 2008-2013 - Ahmad Fauzi, 09.05.52.0068; Puspitasari, Elen (Students Journal of Accounting and Banking, 2014)
This study was conducted to determine the factors that influence initial returns. This study examined the size of the company, profitability, financial leverage, firm age, proportion of ownership of existing shareholders, auditor reputation, underwriter reputation, and price earning ratio of the initial return. This study uses secondary data from the companys initial public offering in 2008 to 2013 were collected by purposive sampling method. Analysis using multiple linear regression analysis. The results found that company size, financial leverage, firm age, underwriter reputation, and price earning ratio and no significant positive effect on initial returns. profitability, proportion of ownership of existing shareholders, auditor reputation and significant negative effect on the initial return. Keywords: profitability, leverage, proportion ofownership ofexisting shareholders, auditor reputation, underwriter reputation andinitial returnÂ